Experimental Study on the Impact of Lubricant on the Performance of Gravity-Assisted Separated Heat Pipe - Rongyang, Yiming; Su, Weitao; Mao, Zujun; Huang, Wenlin; Du, Bowen; Zhang, Shaozhi (Energies (Basel), 2024)
Gravity-assisted separation heat pipes (GSHPs) are extensively utilized in telecommunications base stations and data centers. To ensure year-round cooling, integrating GSHPs directly with a vapor compression refrigeration system is a viable solution. It is unavoidable that the refrigeration system’s lubricant will infiltrate the heat pipe loop, thereby affecting its thermal performance. This paper examines the performance of a GSHP, which features a water-cooled plate heat exchanger as the condenser and a finned-tube heat exchanger as the evaporator, when the working fluid (R134a) is contaminated with a lubricant (POE, Emkarate RL-46H). The findings are compared with those from a system free of lubricant. The experimental outcomes indicate that the presence of lubricant degrades the heat transfer efficiency, particularly when the filling ratio is adequate and no significant superheat is observed at the evaporator’s outlet. This results in a 3.86% increase in heat transfer resistance. When the charge of the working fluid is suboptimal, the average heat transfer resistance remains relatively constant at a 3% lubricant concentration yet increases to approximately 5.27% at a 4–6% lubricant concentration, and further to 12.32% at a 9% lubricant concentration. Concurrently, as the lubricant concentration fluctuates between 3% and 9%, the oil circulation ratio (OCR) varies from 0.02% to 0.11%.